The Influence of Competency, Work Motivation, and Work Discipline on the Performance of the Ground Crew of the Skadron Udara 17 Pangkalan TNI Angkatan Udara Halim Perdanakusuma - Thaariq, Muhammad Magriza Ath; Pujiati, Herni (Dinasti International Journal of Management Science, 2025)
This research aims to prove the influence of competence, work motivation, and work discipline on the performance of Ground Crew in Skadron Udara 17 Pangkalan TNI Angkatan Udara Halim Perdanakusuma. This research uses a quantitative approach, survey methods and path analysis. The population is 130 of Ground Crews. With a simple random sampling technique, 80 respondents were obtained. Data were analyzed using Excel and SPSS version 25.00. The research results show that: Competence has a direct positive and significant effect on work discipline of 0.412; work motivation has a direct positive and significant effect on work discipline of 0.468; competency has a direct positive and significant effect on performance of 0.369; work motivation has a direct positive and significant effect on performance of 0.291; work discipline has a direct positive and significant effect on performance of 0.281. Implications, to increase the performance of Ground Crews in Skadron Udara 17 Pangkalan TNI Angkatan Udara Halim Perdanakusuma to improve the competence, work motivation and work disciplin.